2021
DOI: 10.1007/s42770-021-00557-5
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant Staphylococcus aureus of the clonal lineage ST5-SCCmecII-t2460 was associated with high mortality in a Wuhan hospital

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is an important human pathogen that can cause serious infectious diseases. An emerging MRSA strain, ST5-SCCmecII spa-type-t2460 (SMRSA), has spread rapidly since its recent emergence in China, but little information is available about this lineage. In this study, 91 MRSA isolates were collected from patients treated in the Zhongnan Hospital, Wuhan University, from 2018 to 2019, and investigated for their molecular characteristics, antibiotic resistance profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…In terms of the susceptibility patterns of our MRSA isolates to the tested b-lactam antibiotics, all our investigated strains appeared resistant to oxacillin and cefoxitin; meanwhile, 48% and 4% of the isolates were resistant to ceftriaxone and imipenem, respectively. Consistent with a report from China, all ST239-MRSA strains were resistant to oxacillin and cefoxitin (Li et al, 2021), confirming the isolates as MRSA. Moreover, a previous research paper carried out in Israel revealed that 97.9% of MRSA isolates were sensitive to imipenem (Samba and Gadba, 1993).…”
Section: Discussionsupporting
confidence: 90%
“…In terms of the susceptibility patterns of our MRSA isolates to the tested b-lactam antibiotics, all our investigated strains appeared resistant to oxacillin and cefoxitin; meanwhile, 48% and 4% of the isolates were resistant to ceftriaxone and imipenem, respectively. Consistent with a report from China, all ST239-MRSA strains were resistant to oxacillin and cefoxitin (Li et al, 2021), confirming the isolates as MRSA. Moreover, a previous research paper carried out in Israel revealed that 97.9% of MRSA isolates were sensitive to imipenem (Samba and Gadba, 1993).…”
Section: Discussionsupporting
confidence: 90%
“…MRSA ST5 isolates in Wuhan showed high resistance rate to erythromycin, clindamycin, ciprofloxacin, levofloxacin, moxifloxacin, tetracycline and gentamicin. 49 In shanghai, MRSA ST5 strains show high rate of resistance to penicillin, cefazolin, cefoxitin, erythromycin, fosfomycin, gentamicin, levofloxacin. 50 In Zhejiang, MRSA ST5 strains show high rate of resistance to erythromycin, clindamycin, ciprofloxacin, levofloxacin, tetracycline, and but exhibit low rate of resistance to linezolid, vancomycin, trimethoprim-sulfamethoxazole, rifampicin, tigecycline and gentamicin.…”
Section: Discussionmentioning
confidence: 99%